FINANCIAL RISK MANAGEMENT STRATEGIES FOR STARTUPS IN THE DIGITAL ERA - Erwin; Teti Anggita Safitri; Alfiana; Mohd Syahrin (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Financial Risk Management Strategy for Startups in the Digital Age is an integrated approach used by startup companies to identify, mitigate, and manage financial risks arising in a dynamic digital environment. The strategy includes developing realistic budgets and financial projections, investing in cybersecurity and insurance, and diversifying revenue. The aim is to increase the company's resilience to market fluctuations and digital threats, and achieve sustainable business growth. The study conducted in this research uses the literature research method. The results show that there are three main strategies that can help startups manage financial risks. First, realistic budgeting and financial projections help startups monitor expenses and identify funding needs at each stage of development. Second, investing in adequate cybersecurity and insurance is crucial to protect business and customer data from digital threats and reduce potential financial losses due to data breaches or system failures. Thirdly, revenue diversification helps startups to be more resilient to market fluctuations, allowing companies to be more adaptive and proactive in managing risks.